Estudo para viabilização e implantação da manutenção centrada na confiabilidade utilizando a ferramenta FMEA em uma indústria alimentícia - Falceti, Bruna Labegalini (2022)
The industry is experiencing a continuous evolution and development of its processes, what increases the need of more available resources and reliability of its machinery. Aiming to achieve this higher availability, an analysis of an industry using the methodology FMEA was made to define its critical productive equipment. This study made feasible the identification of failure mode and effect analysis of its machinery. Based on the information collected, the maintenance plan was reviewed to decrease unexpected stops on the process. The implementation of the plan made attainable na increase of availability due the best reliability performance.